Early to mid-Holocene sedimentary environmental evolution in the palaeo-Ningbo Bay, East China and its implications for Neolithic coastal settlement - Lyu, Ye; Xu, Hao; Meadows, Michael E.; Wang, Zhanghua (Frontiers in Marine Science, 2022)
The Ningbo Plain on the East China coast is an important center of Neolithic culture, and associated settlements were influenced by changing sea levels and the geomorphological and hydrological environments of the palaeo-Ningbo Bay, the details of which are still subject to debate. This study is based on two well-dated sediment cores obtained from the Ningbo Plain, and here we report analyses of their sedimentology and foraminifera to reveal the infilling history of the palaeo-Ningbo Bay and its association with Neolithic occupation. The lithology of the largely muddy sediments and the dominance of euryhaline and brackish water foraminiferal species are indicative of an intertidal to a subtidal environment in the palaeo-bay during the early to mid-Holocene. Abrupt coarsening of sediment grain size and a corresponding increase in the abundance of foraminiferal species of inner and middle shelf environments occurred at ca. 8.8 cal. kyr BP and 7.6 cal. kyr BP, reflecting two major events of strengthened marine transgression that correspond to the rapid global sea-level rise events of Meltwater pulses (MWPs) 1C and 1D, respectively. A marked increase in the relative abundance of Ammonia annectens and Ammonia compressiuscula during ca. 7.5–7.1 cal. kyr BP further indicates frequent storm surges at that time. Between the two rapid transgression events, aggradation of tidal flats prevailed after ca. 8.0 cal. kyr BP, which provided a suitable setting for Neolithic settlements, as indicated by the recently discovered Jingtoushan site. However, the transgression sequence associated with the latter, the MWP-1D event, caused a regional cultural interruption at ca. 7.6 cal. kyr BP. Infilling and coastal marsh development in the palaeo-Ningbo Bay occurred progressively after ca. 7.0 cal. kyr BP and are associated with the emergence of the Hemudu culture.